REPERCUSSIONS OF THE COMPETITIVE-PARTICIPATORY DISCOURSES IN PLANNING PRACTICE. A CRITICAL APPROACH - Okten, Ayse Nur; Sengezer, Betul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
Planning discipline has been analyzing the space and the society to discover - or explain-its own raison d'tre, since its early days after the Industrial Revolution, The critical approach to planning has been questioning the power relations underlying the planning process. The aim of this paper is to question why and how the discourses of competitive-participatory planning is converted into a legitimization tool of controversial planning practices, and to review some planning experiences in Turkey in this respect.
Keywords: Critical approach; institutional structuring; pragmatism; power relations; Architecture